Design of the converging stepped spillway of the Toma Grande Dam with 3D numerical modeling - Cántaro Fabián, Gideael Quislón (2023)
This study focuses on the design of a converging variable section stepped spillway using three-dimensional numerical modeling with the objective of finding the optimal hydrodynamic sizing and efficient hydraulic load dissipation in stepped spillways, for which different alternatives were evaluated from a constant section spillway and the hydraulic parameters were compared to determine the appropriate hydraulic operation. The results show that the contraction of the downstream section allows for additional energy dissipation, which is important for improving the hydraulic performance of stepped spillways. The models were calibrated with the laboratory experiment conducted by Arosquipa et al. (2022). These findings open the door for future research and improvements in the design of converging stepped spillways, which is crucial in water resource management in hydraulic projects, especially in critical situations expected due to climate change and without incurring higher costs.